Emic Meaning of Asok Tukon and Dowry in Javanese Marriage Tradition - Nurulliza Fathimatur Rifyan (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
In Javanese tradition, there is a custom that is practiced on the day before the marriage, namely